Music, Dance and Narrative in Rameau's Zaïs: Bringing the Immortal back to Life. (November 2015) - Lalonger, Edith; Williams, Jonathan
Abstract : The year 2014 saw the 250 th anniversary of the death of the leading opera composer of the French Enlightenment, Jean-Philippe Rameau (1683–1764). While none of his 30 operas was granted a full production in the UK, semi-staged performances of three were given in London as part of the Rameau Project by Jonathan Williams and the Orchestra of the Age of Enlightenment. This interdisciplinary collaboration is based at Oxford University and has since 2012 been re-examining performance issues in Rameau's operas. Perhaps most fascinating is their research into stylistically-appropriate dance with Baroque dancer and choreographer, Edith Lalonger. As their UK première of Zaïs given at the QEH in April 2014 highlighted, the impact of dance in these rich and colourful works is extraordinary. One year on, Williams and Lalonger reflect on their experiences of bringing Rameau's magical masterpiece to the London stage.